2002
DOI: 10.1053/rmed.2001.1269
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis obliterans organizing pneumonia in cancer: a case series

Abstract: Bronchiolitis obliterans with organizing pneumonia (BOOP) is an infrequently encountered clinical condition that can mimic a number of other pathologic lung processes. The presentation of this treatable condition in cancer patients has not been described in any large series. We conducted a retrospective study of patients with BOOP at Memorial Sloan-Kettering Cancer Center, NewYork, NY, U.S.A. from January 1992 to December 1999. The type and treatment of primary cancer, clinical and radiographic features of ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 15 publications
5
53
1
Order By: Relevance
“…Organising pneumonia may occur in association with various haematological disorders or malignancies [90,93] including: acute myelomonocytic leukaemia with inversion of chromosome 16 [370]; acute lymphoblastic leukaemia [371]; chronic myelomonocytic leukaemia [372]; myelodysplastic syndrome [354,373,374]; T-cell adult leukaemia [375,376]; Evans syndrome [377]; Ewing sarcoma [371]; Hodgkin disease [371]; and various cancers with or without radiation therapy to the chest [378]. In patients with treated haematological malignancies and suspected invasive pulmonary aspergillosis, open lung biopsy may provide a diagnosis of organising pneumonia in up to ,20% of cases [379].…”
Section: Fungimentioning
confidence: 99%
“…Organising pneumonia may occur in association with various haematological disorders or malignancies [90,93] including: acute myelomonocytic leukaemia with inversion of chromosome 16 [370]; acute lymphoblastic leukaemia [371]; chronic myelomonocytic leukaemia [372]; myelodysplastic syndrome [354,373,374]; T-cell adult leukaemia [375,376]; Evans syndrome [377]; Ewing sarcoma [371]; Hodgkin disease [371]; and various cancers with or without radiation therapy to the chest [378]. In patients with treated haematological malignancies and suspected invasive pulmonary aspergillosis, open lung biopsy may provide a diagnosis of organising pneumonia in up to ,20% of cases [379].…”
Section: Fungimentioning
confidence: 99%
“…Other causes of pneumonia were considered and ruled out in most patients. The histological data and course excluded pulmonary lymphoma relapse, lymphoma-related organising pneumonia [45], rheumatoid lung disease and other respiratory diseases. Doubtful cases were excluded [14][15][16].…”
Section: Causalitymentioning
confidence: 99%
“…The occurrence of BOOP in association with malignancy including lung cancer has been reported [2,5]. The pathological finding of organizing pneumonia adjacent to a resected lung tumor was actually common.…”
Section: Discussionmentioning
confidence: 99%
“…Arrabal Sanchez et al reported a case of adenocarcinoma found in a patient at a different part of his lung during thoracoscopic lung biopsy for a lung lesion, which was diagnosed as BOOP [5]. In a study by Mokhtari et al, among 43 cases of BOOP in association with cancer, 10 were associated with lung cancer but they all had received treatment in the form of chemotherapy and/or radiotherapy [2]. The occurrence of BOOP immediately after resection of lung cancer without adjuvant therapy, to the best of our knowledge, has never been reported in literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation